2004
DOI: 10.1088/0305-4470/37/41/008
|View full text |Cite
|
Sign up to set email alerts
|

Geometry and Hamiltonian mechanics on discrete spaces

Abstract: Numerical simulation is often crucial for analysing the behaviour of many complex systems which do not admit analytic solutions. To this end, one either converts a 'smooth' model into a discrete (in space and time) model, or models systems directly at a discrete level. The goal of this paper is to provide a discrete analogue of differential geometry, and to define on these discrete models a formal discrete Hamiltonian structure-in doing so we try to bring together various fundamental concepts from numerical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…[10,11]. The first requirement is to choose an appropriate discrete analogue for the reals R. We can use discrete lattices (which have a ring structure), or the space of floating point numbers F which have a quasi-ring (cf.…”
Section: Geometry and Hamiltonian Mechanics On Discrete Spacesmentioning
confidence: 99%
See 3 more Smart Citations
“…[10,11]. The first requirement is to choose an appropriate discrete analogue for the reals R. We can use discrete lattices (which have a ring structure), or the space of floating point numbers F which have a quasi-ring (cf.…”
Section: Geometry and Hamiltonian Mechanics On Discrete Spacesmentioning
confidence: 99%
“…The first requirement is to choose an appropriate discrete analogue for the reals R. We can use discrete lattices (which have a ring structure), or the space of floating point numbers F which have a quasi-ring (cf. [10,11]) structure. Since computers uses floatingpoint numbers, and since our main focus is numerical simulation, F will be our choice.…”
Section: Geometry and Hamiltonian Mechanics On Discrete Spacesmentioning
confidence: 99%
See 2 more Smart Citations
“…Either we can discretize continuous systems (there exist a wide variety of techniques for doing so), or we can directly model at the discrete level itself. In previous work [6], [7], [8], [9], [10] we developed a methodology to model physical systems directly at the discrete (in space and time) level and we showed that the discrete models which we obtain as a result of our modeling process exactly coincide with discretized models!, thus offering an alternative approach towards the simulation of port-Hamiltonian systems.…”
Section: Introductionmentioning
confidence: 85%